Failure of Splenectomy to Ameliorate Portal Hypertension in Myeloproliferative Disorders - Samuel S Lee; Guido Van Rosendaal; Thomas E Lay; James K Kelly; Graham F Pineo (Canadian Journal of Gastroenterology)
The correct treatment of portal hypertension associated with myeloproliferative disorders remains uncertain. Splenectomy has been advocated by some to eliminate the forward flow component of the portal hypertension and thus reduce portal pressure. The authors describe three recent cases of myeloproliferative disorder in whom splenectomy failed to achieve any significant amelioration of portal hypertension, with in-depth hemodynamic studies in one patient. Based on these experiences, the authors suggest that splenectomy is not the optimum treatment of the portal hypertension associated with myeloproliferative disorders.